L’évolution du Devoir vue à travers les structures de son contenu - Jean de Bonville; Cyntia Darisse (Communication)
This article describes how the editorial content of Montreal’s Le Devoir has changed from the year of its foundation in 1910 until the early 21st century. The analysis of four of their structural dimensions allows the authors to answer the following questions: Who wrote the articles? What topics are dealt with? What geographical or geopolitical areas are covered? What journalistic genres are practised?